A fast settling frequency synthesizer with switched‐bandwidth loop filter. (19th March 2021) - Beiraghdar, Farhad; Ghobadi Rad, Alireza; Sheikhaei, Samad; Tohidian, Massoud
Summary: This paper presents a new method to substantially decrease the settling time of analog phase‐locked loops (PLLs) while keeping its phase noise unaffected. This is achieved by switching the loop filter capacitors and resistor in such a way that output frequency is kept seamless. This method only affects the loop filter architecture and does not need any other changes to other blocks of the PLL. A frequency synthesizer circuit is implemented to validate the proposed method. The reference synthesizer has a 342‐μs settling time for a 1‐GHz frequency step (1.5 to 2.5 GHz), while if the proposed technique is enabled, the settling time is reduced to 48 μs (worst case). The measured phase noise of the synthesizer at 10‐kHz offset from a 2‐GHz carrier is −110 dBc/Hz. Abstract : This paper presents a new method to substantially decrease the settling time of analog phase‐locked loops (PLLs) while keeping its phase noise unaffected. This is achieved by switching the loop filter capacitors and resistor in such a way that output frequency is kept seamless. This method only affects the loop filter architecture and does not need any other changes to other blocks of the PLL.